2008
DOI: 10.1037/a0013113
|View full text |Cite
|
Sign up to set email alerts
|

Automatic associations and panic disorder: Trajectories of change over the course of treatment.

Abstract: Cognitive models of anxiety and panic suggest that symptom reduction during treatment should be preceded by changes in cognitive processing, including modifying the anxious schema. The current study tests these hypotheses by using a repeated measures design to evaluate whether the trajectory of change in automatic panic associations over the course of 12-week cognitive behavior therapy (CBT) is related to the trajectory of change in panic symptoms. Individuals with panic disorder (N=43) completed a measure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 70 publications
8
103
1
1
Order By: Relevance
“…This would be in line with neuroimaging research showing that while both low and high anxious individuals respond to taskrelevant threat stimuli with increased activity in the amygdala, which has been shown to play a key role in the acquisition and extinction of fear (Davis, 2002;LeDoux, 2000), only anxious participants also show amygdala hypersensitivity for task-irrelevant threat (Bishop, Duncan, & Lawrence, 2004). This explanation would also be consistent with previous studies reporting CBT induced bias changes, having used implicit evaluation tasks (Teachman et al, 2008;Teachman & Woody, 2003) or emotional stroop tasks, where participants name the colour of threat-related words (Mogg et al, 1995;Van den Hout et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This would be in line with neuroimaging research showing that while both low and high anxious individuals respond to taskrelevant threat stimuli with increased activity in the amygdala, which has been shown to play a key role in the acquisition and extinction of fear (Davis, 2002;LeDoux, 2000), only anxious participants also show amygdala hypersensitivity for task-irrelevant threat (Bishop, Duncan, & Lawrence, 2004). This explanation would also be consistent with previous studies reporting CBT induced bias changes, having used implicit evaluation tasks (Teachman et al, 2008;Teachman & Woody, 2003) or emotional stroop tasks, where participants name the colour of threat-related words (Mogg et al, 1995;Van den Hout et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
“…Foa, Huppert, & Cahill, 2006;Williams, Watts, MacLeod, & Mathews, 1997). This assumption is supported by a large number of studies showing an association between heightened states of anxiety and bias, using paradigms that tap into different aspects of information processing: compared to non-anxious controls, anxious individuals show threat-favouring processing biases in attention (for a review, see Mathews & MacLeod, 2005) and visual working memory (VWM; Reinecke, Becker, & Rinck, 2009;Reinecke, Rinck, & Becker, 2006;Reinecke, Rinck, & Becker, 2008), more negative implicit evaluation of fear material (Huijding & de Jong, 2009;Reinecke, Becker, Hoyer, & Rinck, 2010;Teachman, Marker, & Smith-Janik, 2008), and stronger avoidance tendencies in reaction-time based approach-avoidance tasks (Reinecke, Becker, Hoyer, & Rinck, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…This is the first study that compares the level of cognitive mediation in purely behavioral versus cognitive-behavioral treatment of specific phobia. Previous studies have already demonstrated cognitive mediation of treatment in purely behavioral exposure formats and cognitive-behavioral treatments separately (Hofmann, 2004;Hofmann et al, 2007;Teachman, Marker, & Smith-Janik, 2008;Vögele et al, 2010). Therefore, we expect significant cognitive mediation of treatment outcome in both the BE and the EXP group.…”
Section: Mechanisms Of Change In Exposurementioning
confidence: 61%
“…Therefore, the notion that "implicit cues" (heuristic information) are more likely to affect implicit evaluations, whereas "explicit cues" (elaborative processing) are more likely to affect explicit evaluations -while intuitively satisfying -may be wrong. The key insight is that as a predictor, implicit evaluations may influence behavior through subtle, heuristic means, but as an outcome, implicit evaluations may also be shaped more by overt, elaborative efforts to create, change, or override existing associations (see also Teachman, Marker, & Smith-Janik, 2008 More speculatively, the current results may shed some light on the longevity of attitude change. Specifically, although source characteristics have been shown to operate both at more and less thoughtful levels, the resultant evaluations are stronger (i.e., longer lasting, more resistant, more predictive of behavior) when people engage in more elaboration during the persuasion attempt (Petty, Haugtvedt, & Smith, 1995).…”
Section: Source Credibility 25mentioning
confidence: 88%